Infertility Care: Bridging the Emotional and Physical Gaps in Gynecological Nursing - John Shiju, Dolly (International Journal of Nursing Research, 2024)
Infertility is a complex medical condition defined by the inability to achieve a clinical pregnancy after 12 months of regular and unprotected sexual intercourse, impacting approximately 8–12% of reproductive-aged couples worldwide.[1] This multifaceted issue presents a range of psychological, physical, mental, spiritual, and medical challenges for individuals and their partners, often leading to significant emotional and relational strain.[2] While male infertility is an important aspect of infertility discussions, this editorial will specifically focus on female infertility. Understanding fecundability, or the probability of conceiving within a single menstrual cycle, is essential for effective management and treatment.